2015
DOI: 10.1038/nphoton.2015.93
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cascade laser frequency stabilization at the sub-Hz level

Abstract: High-precision measurements with molecules may refine our knowledge of various fields of physics, from atmospheric and interstellar physics to the standard model or physics beyond it. Most of them can be cast as absorption frequency measurements, particularly in the mid-infrared 'molecular fingerprint' region, creating the need for narrow-linewidth lasers of well-controlled frequency. Quantum cascade lasers provide a wide spectral coverage anywhere in the mid-infrared, but show substantial free-running frequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 53 publications
0
117
0
Order By: Relevance
“…Optical frequency transfer by the active noise cancellation (ANC) method [1,12] has a wide range of applications, including remote high-resolution and high-accuracy spectroscopy [13][14][15], very long baseline interferometry [16], and remote narrow-linewidth light sources [2,14,17]. However, if only a comparison of the optical frequencies is required, the recently proposed two-way method [18][19][20] offers a good alternative with the advantage of simplified experimental apparatus without active components.…”
Section: Introductionmentioning
confidence: 99%
“…Optical frequency transfer by the active noise cancellation (ANC) method [1,12] has a wide range of applications, including remote high-resolution and high-accuracy spectroscopy [13][14][15], very long baseline interferometry [16], and remote narrow-linewidth light sources [2,14,17]. However, if only a comparison of the optical frequencies is required, the recently proposed two-way method [18][19][20] offers a good alternative with the advantage of simplified experimental apparatus without active components.…”
Section: Introductionmentioning
confidence: 99%
“…These features lead to their wide adoption for spectroscopic applications in the mid-IR region. However, their free running linewidth is subject to undesired noise that makes their frequency stabilization challenging8. High finesse optical cavities have the potential for substantial reduction of laser noise910 and have been recently investigated11.…”
mentioning
confidence: 99%
“…Indeed, in the last years, OFLs have shown undoubted effectiveness in comparing remote atomic clocks beyond the ultimate limit of GPS-based comparisons, attaining precision levels not limited by the frequency transfer method [191][192][193][194][195][196], and are also envisioned as key elements for the development of a new kind of high-accuracy relativistic geodesy [195,197]. Besides optical clock comparisons, short-range OFLs have recently been exploited in order to increase the spectral performance of a local laser and to allow for precision molecular spectroscopy [198]. It has been recently demonstrated that long-haul fiber-based optical frequency dissemination is a reliable tool for remote end users to perform high-precision procedures well beyond the ultimate capabilities of GPS dissemination [199].…”
Section: Frequency Referencing Improvementmentioning
confidence: 99%